(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explores the advancements in the design and performance of an improved compression moulding machine aimed at efficiently recycling various plastic wastes, with an emphasis on Polyethylene Terephthalate (PET). With global plastic waste accumulation posing severe environmental challenges, enhancing recycling technologies is imperative. The re-designed machine was tested at operating temperatures of 200°C, 250°C, and 300°C, highlighting the critical role of temperature and processing duration in determining product quality. Theoretical heating times were found to be shorter than actual times due to real-world inefficiencies such as heat loss and thermal conductivity variations. Weight loss during heating, attributed to the evaporation of volatile components and thermal degradation, was observed. The formation of air pores in samples with extended heating times underscored the necessity for precise process control. The PET melting process initiated effectively at approximately 250°C. The improved machine demonstrated significant potential in enhancing recycling efficiency and versatility.